APLIKASI ARANG KULIT KAYU SEBAGAI CAMPURAN MEDIA TUMBUH ANAKAN Eucalyptus urophylla dan Acacia mangium - Gusmailina Gusmailina; Gustan Pari; Sri Komarayati (Jurnal Penelitian Hasil Hutan, 2002)
One of the alternatives that can be used to develop and have significant prospect to improve the critical or degraded land is through the use or application of charcoal. Charcoal can be used as one ingredient in the media to enhance the growth of plants. particularly still at seedling stage and at the field preparation as well. The application of charcoal sould when they are increase soil pH and improve water and air circulation in the soil, there by stimulating the growth of root and the plants.This report deals with research results of applying two kinds of wood-bark charcoal, i.e. bark charcoal from tusam (Pinus merkusii) and mangium (Acacia mangium), on the media for the growth of Eucalyptus urophylla and Acacia mangium seedlings up to 4,5-month period, respectively. The main objective of this research trial was to assess the effect of applying wood-bark charcoal on the growth of the seedlings. The two kinds of wood-bark charcoal were added at varying concentrations, i.e. 10%, 20%, 30%, 40%, and 50 percent, and 0% as control.The research revealed that the use of both kinds of wood-bark charcoal at 10-30 percent turned out to he the most optimal or suitable for the growth of the two seedlings. For height growth of Acacia mangium seedlings, the best effect was at the application of 10 percent tusam's wood-bark charcoal, where the height increase in the Acacia mangium seedling reached 13.01 percent. i.e.1.9 times greater than the height growth of the control. About the increase in the diameter of the seedling, the best effect was at 10 percent and 20 percent of either tusam's or mangium's wood-bark charcoal. Such diameter increase were almost similar i.e. 0.45 cm and 0.42 cm for tusam's and mangium's wood-bark charcoals, consecutively.For the height growth of Eucalyptus urophylla seedlings, the best effect was at the application 20 percent of tusam's wood-bark charcoal and 30 percent of mangium's wood bark charcoal. The height increases were at 20 percent tusam's wood-bark charcoal and 30 percent mangium's wood-bark charcoal, i.e. consecutively 1.38 and 1.35 times greater than that of the control. Similar phenomena as occurred to in the height increase in Eucalyptus urophylla seedlings also found in the diameter increases of the corresponding seedlings. In this situation, the height increclse was 0.56 cm. The use of tusam's wood-bark charcoal at JO percent offered the best effect on the growth development ofE. urophylla and A. mangium seedlings, i.e. 0.913 grams and 0.496 grams, respectively.